2009
DOI: 10.1111/j.1365-2036.2009.04004.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: adherence to medication for chronic hepatitis C – building on the model of human immunodeficiency virus antiretroviral adherence research

Abstract: SUMMARY Background Treatment of hepatitis C virus (HCV) infection with pegylated interferon/ribavirin achieves sustained virological response in up to 56% of HCV mono-infected patients and 40% of HCV/human immunodeficiency virus (HIV)-co-infected patients. The relationship of patient adherence to outcome warrants study. Aim To review comprehensively research on patient-missed doses to HCV treatment and discuss applicable research from adherence to HIV antiretroviral therapy. Methods Publications were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 104 publications
(197 reference statements)
1
53
0
Order By: Relevance
“…In terms of medication adherence, several studies examined adherence to HCV treatment [48]. Using selfreport, 69% to 98% of HCV-positive individuals reported being adherent to their medications, whereas 74% to 92% were adherent when measured by electronic devices [48].…”
Section: Implications For Daily Livingmentioning
confidence: 99%
“…In terms of medication adherence, several studies examined adherence to HCV treatment [48]. Using selfreport, 69% to 98% of HCV-positive individuals reported being adherent to their medications, whereas 74% to 92% were adherent when measured by electronic devices [48].…”
Section: Implications For Daily Livingmentioning
confidence: 99%
“…Research has consistently shown that health professionals’ assessment of adherence to HIV medication is overestimated unless a validated assessment tool is used 55. Several studies have demonstrated the benefits of interdisciplinary care including nurses and pharmacists on patient adherence to hepatitis C treatment 56–58.…”
Section: Interventions To Support Adherencementioning
confidence: 99%
“…Strategies including implementing culturally appropriate education individualized to the patient’s level of health literacy, increasing social support, providing medication reminder tools, strengthening the patient–health care provider relationship, and offering directly observed treatment (DOT) have all been shown to be successful 55. A systematic review of patient adherence to IFN-based treatment for hepatitis C concluded that the highest adherence rates were reported in studies that used patient self-report strategies to measure adherence, whereas the lowest rates were reported in studies using pharmacy refill claims 62…”
Section: Interventions To Support Adherencementioning
confidence: 99%
“…Interestingly, clinical trials have shown that adherence levels tend to decrease over time [19,31]; we show that more doses are needed to compensate for missed doses that occur later in treatment because of the rebound of target cells. While many previous studies have focused on average adherence [18,19,[29][30][31]36], we emphasize that the timing of the missed doses is also a critical determinant of treatment outcome and the risk of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Although high rates of sustained virological response have been achieved in clinical trials, adherence levels may vary substantially among the vast population of infected patients, owing to long treatment periods, complicated regimens associated with DAA combination therapies and limited access to health care [18,19,[29][30][31]. Rational design of combination therapy that achieves viral eradication in patients and maximizes the durability of available DAAs in the presence of suboptimal adherence is a research priority [18,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%